Pendidikan Islam di Indonesia dalam Kajian Ilmu Sejarah: Perkembangan, Pengaruh, dan Eksistensi terhadap Kehidupan Masyarakat Indonesia - Anggoro, Nur; Prakosa, Ikhwan; Pramono, Muhammad; Ramadhan, Fauzan Syahru (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
This article focuses on studying Islamic education in Indonesia in the study of historical science which includes development, influence, and existence on the lives of Indonesian people. The background of Islamic education in Indonesia is influenced by the spread of Islam. Islamic education teaches about knowledge and behavior that is in accordance with the teachings and values of the Islamic religion. The teachings of the Qur'an and Hadith are the main teachings of Islamic education methods. Therefore, this article aims to examine the history of Islamic education in Indonesia. The method used in compiling this article is the historical method. This method is carried out in four stages, namely heuristics, criticism, interpretation and historiography. From this research it can be seen that Islamic education in Indonesia is colored with a touch of culture, customs and habits of the people of each region. Islamic education in Indonesia is developed through Islamic boarding schools, madrasas, and langgar. Islamic education does not only study religious knowledge, but also other fields of knowledge that are directed according to Islamic teachings.